Analysis of Child-Friendly School Strategies to Prevent Bullying at Elementary Schools - Halimatus Sa'diyah; Sri Nurhayati (AL-ISHLAH: Jurnal Pendidikan, 2023)
Bullying is aggressive behavior that affects children’s social development. The number of bullying cases in Indonesia shows that schools as educational institutions have not been able to provide optimal protection for students. A child-friendly school model is expected to reduce bullying at schools in Indonesia. This research aimed to analyze child-friendly school strategies to reduce bullying at elementary schools. It used a qualitative approach with descriptive analysis whose instrument adopted a child-friendly school model developed by UNICEF. The data were collected through interviews, observation, and documentation. There are 73 participants in this research, including the headmaster, teachers, students and parents chosen by random sampling technique. The technique for data analysis included data condensation, data display, and drawing conclusions. The results showed that child-friendly school efforts to reduce bullying included several aspects that adapted to the model developed by UNICEF. The strategies applied to reduce bullying were through life skills-based learning activities (public speaking and gardening) and character-based learning activities (reciting the Qur'an and praying in congregation). In conclusion, the strategies of a child-friendly school in anticipating bullying in elementary school can be done by developing life skill education and various character based learning activities.